Target the pathways to scale out climate-smart agricultural technologies to farming communities - Mwongera, Caroline; Mwungu, Chris Miyinzi; Läderach, Peter R.D.; Acosta, Mariola; Ampaire, Edidah L.; Eitzinger, Anton; Lamanna, Christine; Shikuku, Kelvin Mashisia; Twyman, Jennifer; Winowiecki, Leigh Ann (International Center for Tropical Agriculture, 2017)
The process of getting climate-smart agricultural (CSA) interventions and practices to farmers is just as important as the interventions and practices.